2013
DOI: 10.4236/ajac.2013.49065
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Zinc from Aqueous Solutions Using Modified Brazilian Gray Clay

Abstract: In this study, the removal of zinc (Zn 2+ ) from aqueous solutions was investigated using a Na-enriched Brazilian gray clay. The mineral clays were characterized through EDX, XRD analysis and CEC. A finite bath system was used to evaluate the main effects of mechanical agitation (from 100 to 200 rpm), pH values in the range from 6.0 to 8.0 and Zn 2+ initial concentrations (from 10 to 50 mg/L) on the removal process capacity. Langmuir and Freundlich isotherm models were applied in order to determine the efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
(37 reference statements)
2
12
0
3
Order By: Relevance
“…It means that the proposed model adjusts the experimental data and, therefore, the kinetics of zinc ion adsorption on SIG untreated clay follows the pseudo-second-order model. This behavior agrees very well with other studies presented in the open literature regarding to experimental results of heavy metals removal [17,37,38].…”
Section: Pseudo-second-order Reaction Kineticsupporting
confidence: 92%
See 2 more Smart Citations
“…It means that the proposed model adjusts the experimental data and, therefore, the kinetics of zinc ion adsorption on SIG untreated clay follows the pseudo-second-order model. This behavior agrees very well with other studies presented in the open literature regarding to experimental results of heavy metals removal [17,37,38].…”
Section: Pseudo-second-order Reaction Kineticsupporting
confidence: 92%
“…Vasconcelos et al [17] found 89.53% with Na-enriched gray clay in a finite bath system under the following process conditions: agitation of 150 rpm, pH of 8 and temperature of 27˚C for 5 h.…”
Section: Effect Of Contact Timementioning
confidence: 99%
See 1 more Smart Citation
“…The method of adsorption is widely used because of its easy function, low level of energy consumption, simple preservation, high capacity of adsorption and high efficiency for water and wastewater treatment (Jain et al 2015). This method makes use of various adsorbent like activated carbon, charcoal ashes, bentonite, clay, algaes, raw crab shell and bacteria (Wan Ngah et al 2011;Ahlam et al 2012;Patricia et al 2013;Haider et al 2014;Karnib et al 2014;Chuanqiang et al 2016). Recently, due to their availability, cost effectiveness and lack of toxicity, biopolymers have been adsorbent a proper adsorption of heavy metals by researchers (Haider et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Kaolinite, montmorillonite, and their poly and tetra butyl ammonium derivatives were used for removing Cd (II) from aqueous solution [11]. The removal of metal ions from aqueous solutions by adsorption has been reported by various studies: Pb(II), Zn(II), Cd(II), and Cu(II) onto natural clay [12]; radio nuclides (137Cs) on kaolinite [13]; Pb(II), Cu(II), Fe(III), Mn(II), and Zn(II) onto kaolinite clay [14]; Cd(II), Cu(II), Pb(II), and Zn(II) onto waste calcite sludge [15]; Zn(II), Cd(II), Pb(II), and Cu(II) onto natural Jordanian zeolite [16]; Pb(II), Cu(II), Cd(II), and Ni(II) onto Iranian natural zeolite [17]; Pb(II) and Cd(II) onto clay mineral beidellite [18]; and Zinc(II) onto modified Brazilian gray clay [19].…”
mentioning
confidence: 99%